Light-induced conical intersections: topological phase, wave packet dynamics, and molecular alignment - Halász, Gábor J.; Cederbaum, Lorenz S. (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2011)
In previous publications (J. Phys. B: At., Mol. Opt. Phys. 2008, 41, 221001; J. Phys. B: At., Mol. Opt. Phys. 2011, 44, 045603) a novel and physically interesting phenomenon was found in the ﬁeld of lightÀmatter interactions. It was shown theoretically that exposing a molecule to a laser ﬁeld can give rise to the appearance of so-called light-induced conical intersections (LICIs). The existence of such LICIs may change signiﬁcantly the ﬁeld free physical properties of a molecular system. In this article we review the LICIs in diatomics and provide a new insight to the LICI phenomenon. The sodium dimer is chosen as an explicit sample system. We calculated the Berry phase for a contour that surrounds the point of LICI and found it to be π, which is the same value as for the case of a “natural” CI in triatomic or larger molecules. We also present results to stress the impact of LICIs on molecular wave packet dynamics and molecular alignment in diﬀerent electronic states.